An Optimization Of Carbonized Empty Fruit Bunch Briquettes And Biomass Producer Gas Quality Characteristics Using Response Surface Method (Rsm) - Khairuzi, Muhammad Haris (Universiti Sains Malaysia, 2021)
The global issue of fossil fuel depletion has prompted Malaysia to look for alternate sources of energy that are both renewable and economical, making biomass briquettes one of the best options for mitigating this depletion. In fact, Empty Fruit Bunch (EFB) is one of the most common agricultural wastes in Malaysia, and its briquettes have the potential to be used as an alternative gaseous fuel. However, in developing biomass briquette from EFB, a pre-treatment process is required since it possesses several unwanted characteristics that limits its quality as a good source of fuel. In this study, the composition of binder (organic and inorganic) and water was analyzed to find the best mix of EFB briquettes after pre-treatment. Tapioca starch was used as an organic binder in this work, whereas calcium hydroxide Ca(OH)2 was used as an inorganic binder. Furthermore, proximate analysis, physical analysis, and calorific values were used to determine the properties of different binder mixtures on EFB briquettes. The results were initially compared in terms of the type of binders used to determine the best qualities of EFB briquettes. Because it has a moderate physiochemical and physical analysis, the results show that Mixture 2 briquettes have the best EFB blending. In comparison to inorganic, it has less fixed carbon but also less ash. Less ash means fewer negative effects on the environment and fewer issues with the equipment. Besides, the HHV of OBMixture 2 briquettes is moderate at 22.10 MJ/kg, but there is no significant difference between it and other mixtures. The optimal qualities are then investigated further using statistical and mathematical tools, such as RSM. The best factor and response were identified, and they will be used in the next study. Overall, it was discovered that the optimal mix of carbonized EFB, binder, and water can increase the quality of EFB briquettes and lead to optimal biomass producer gas.